SECURE CREDENTIAL MANAGEMENT IN CLOUD DATABASES USING AZURE KEY VAULT INTEGRATION - Hari Babu Dama (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY, 2025)
The study looks into how securely managing keys and access for cloud-based databases in Azure Key Vault can be achieved. It investigates the risks present in DevOps, designs a protected structure, and tests how it works in the real world. Comparing Aviatrix to various third-party solutions and using empirical data shows better compliance, fewer issues, and easy handling of secrets across multiple clouds.